Assessing the health literacy of caregivers in the pediatric intensive care unit: a mixed-methods study - Reddy, Anireddy R.; Doshi, Anushree K.; Mak, Allison; Shea, Judy A.; Fardad, Joana T.; Moon, Jiwon; Hu, Paula; Garcia-Marcinkiewicz, Annery G. (Frontiers in Pediatrics, 2023)
Background: Limited health literacy is associated with increased hospitalizations, emergency visits, health care costs, and mortality. The health literacy levels of caregivers of critically ill children are unknown. This mixed-methods study aims to quantitatively assess the health literacy of caregivers of children admitted to the pediatric intensive care unit (PICU) and qualitatively describe facilitators and barriers to implementing health literacy screening from the provider perspective. Methods: Caregivers of patients admitted to our large, academic PICU (between August 12, 2022 and March 31, 2023) were approached to complete a survey with the Newest Vital Sign (NVS), which is a validated health literacy screener offered in English and Spanish. We additionally conducted focus groups of interdisciplinary PICU providers to identify factors which may influence implementation of health literacy screening using the Consolidated Framework for Implementation Research (CFIR) framework.Results: Among 48 surveyed caregivers, 79% demonstrated adequate health literacy using the Newest Vital Sign screener. The majority of caregivers spoke English (96%), were mothers (85%), and identified as White (75%). 83% of caregivers were able to attend rounds at least once and 98% believed attending rounds was helpful. Within the PICU provider focus groups, there were 11 participants (3 attendings, 3 fellows, 2 nurse practitioners, 1 hospitalist, 2 research assistants). Focus group participants described facilitators and barriers to implementation, which were mapped to CFIR domains. Timing of screening and person administering screening were identified as modifiable factors to improve future implementation.We found the health literacy levels of PICU caregivers in our setting is similar to prior assessments of parental health literacy. Participation in morning rounds was helpful for developing understanding of their child's illness, regardless of health literacy status. Qualitative feedback from providers identified barriers across all CFIR domains, with timing of screening and person administering screening as modifiable factors to improve future implementation.